Regional fire-greening positive feedback loops in Alaskan Arctic tundra - Chen, Dong; Fu, Cheng; Jenkins, Liza K; He, Jiaying; Wang, Zhihao; Jandt, Randi R; Frost, Gerald V; Bredder, Allison; Berner, Logan T; Loboda, Tatiana V (Nature plants, 2024)
Arctic tundra has experienced rapid warming, outpacing global averages, leading to significant greening whose primary drivers include widespread shrubification. Here we confirm that a fire-greening positive feedback loop is evident across the Alaskan tundra, and evidence suggests that this feedback loop is dominated by the fire-shrub interactions. We show that tundra wildfires, especially those with higher severity, play a critical role in boosting the overall greening of the tundra, often by enhancing upright deciduous shrub growth or establishment but sometimes by inducing increases in other vascular biomass. In addition, fire-greening interactions vary greatly within different tundra subregions, a likely consequence of the spatial heterogeneity in vegetation composition, climatic and geophysical conditions.